Interactive Homework Exercises for Yourng Learners in ELT - Mikulová, Jana (Univerzita Pardubice, 2012)
This bachelor thesis is dealing with interactive homework exercises in English language teaching. It focuses on young learners, learners of lower grades of elementary school. The theoretical part describes young learners, their specific characteristics and needs and suggests suitable activities for these learners. This part focuses on interactive homework exercises provided by modern technologies in English language teaching. It explains the term "interactivity" and it describes advantages and disadvantages of using modern technologies for assigning interactive homework exercises. The practical part defines criteria for the evaluation of interactive homework exercises assigned to young learners in English language teaching and afterwards it evaluates one randomly chosen exercise according to developed evaluation criteria.
Interaktivní domácí cvičení v ELT
Keywords: žáci prvního stupně základní školy; výuka anglického jayka; domácí úkol; interaktivita; young learners; English language teaching; homework; modern technologies; interactivity